Experimental chemistry during emergency remote teaching arising from Covid-19 - Sousa, Leonardo Gomes de (2021)
Experimentation is a fundamental approach in teaching Chemistry, as its use provides not only a better understanding of the content, but also an improved view of science. The present work presents an adaptation of the practical methodology in the emergency remote teaching of Chemistry in Covid-19 times. In order to alleviate the losses in education arising from the pandemic period, videos of practices were used, recorded by the monitor of the general chemistry course, and PhET simulations were used as strategies during classes. The experimentation activities developed along with the questionnaire applied to students in a quali-quantitative way proved to be a great challenge, due to the various difficulties and limitations presented by the students. However, the applied methodological resources helped in the teaching and learning of the studied subjects, being evaluated as satisfactory.